Octahedral Cu2O@Co(OH)2 Nanocages with Hierarchical Flake‐Like Walls and Yolk‐Shell Structures for Enhanced Electrocatalytic Activity. Issue 10 (23rd April 2019) - Sheng, Jiali; Chen, Jiahui; Kang, Jiahui; Yu, Yan; Yan, Ning; Fu, Xian‐Zhu; Sun, Rong; Wong, Ching‐Ping
Abstract: Unique octahedral yolk‐shell Cu2 O@Co(OH)2 nanocages are synthesized by a facile Cu2 O self‐templated strategy as efficient glucose oxidation electrocatalysts. Amorphous Co(OH)2 nanoflakes are formed as octahedral shells through coordinating etching conversion from part of Cu2 O templates. The un‐etched crystalline Cu2 O octahedrons are then remained as cores and voids exist between the cores and shells. The special structure endow these yolk‐shell heterostructure nanocages with abundant active sites, large surface area, and synergistic effect between Cu2 O and Co(OH)2 . The octahedral yolk‐shell Cu2 O@Co(OH)2 nanocages demonstrate superior electrocatalytic activity for glucose oxidation in terms of high sensitivity of 1340 μA cm −2 mM −1, low detection limit of 2 μM, wide linear sensing range, and long‐term stability. This strategy might shed lights on the synthesis of various yolk‐shell heterostructure nanocages with controllable structures and enhanced catalytic performances. Abstract : Yolk‐shell nanocages : Unique octahedral yolk‐shell Cu2 O@Co(OH)2 nanocages composed of crystalline Cu2 O core and amorphous Co(OH)2 shell are fabricated by a facile Cu2 O self‐templated strategy at room temperature. The as‐prepared yolk‐shell Cu2 O@Co(OH)2 nanocages demonstrate superior electrocatalytic activity for glucose oxidation due to the sufficient active sites and large surface area, synergistic effect between Cu2 O and Co(OH)2, which are benefited from the special yolk‐shell nanocages.